Sintesis Nanopartikel Zno/Al2(So4)3 Dengan Metode Mechanical Alloying Sebagai Katalis Limbah Cair Untuk Meningkatkan Ketersediaan Air - Vika Sri Anti; Heryanto Heryanto; Dahlang Tahir (Lambung Mangkurat University Press, 2022)
ZnO/Al2(SO4)3 synthesized by mechanical alloying method (1, 10, and 15 hours) was applied as methylene blue (MB) photodegradation. Fourier transform infrared (FTIR), X-Ray Diffraction (XRD), and Uv-Visible (Uv-Vis) were used to characterize the Physico-chemical properties of the composites. The results of XRD and FTIR characterization showed an average crystal size of 50.02 nm and the lowest transmittance value (%) at 10 hours milling, the degradation efficiency was much influenced by crystallinity speed, functional groups, and milling time. In this study, the optimal degradation based on the results of the Uv-Vis was shown by the sample ZnO/Al2(SO4)3 for 10 hours milling with a degradation percentage of 84.87%. Furthermore, it was found a ZnO/Al2(SO4)3 composite with a very short degradation time of 20 minutes. In order to reduce water pollution in environments, composite based on natural material is a promising solution due to their ability to break up pollutant radical compounds bonding.